Introduction to fuzzy systems - Chen, G. (Guanrong); Pham, Trung Tat (Chapman & Hall/CRC, 2006)
Introduction to Fuzzy Systems provides students with a self-contained introduction that requires no preliminary knowledge of fuzzy mathematics and fuzzy control systems theory. Simplified and readily accessible, it encourages both classroom and self-directed learners to build a solid foundation in fuzzy systems